Análisis energético y exergético de un sistema de producción de energía a través de ciclos de potencia Brayton con interenfriamiento, recalentamiento y regeneración (2021)
In the present work, a mass, energy and exergy balance is carried out for a Brayton power generation cycle in order to evaluate the relationship between the compression ratio (RC) and the efficiency of the cycle, as well as the losses due to irreversibilities. regarding the fuel used. A computational tool is developed, studying the variables and parameters that influence the power cycle and each of the processes that compose it (compression, combustion and expansion). To carry out this objective, it is necessary to carry out a mass, energy and exergy balance for each piece of equipment that is part of the system. Analyzes will be performed at a simple Brayton power cycle as well as a Brayton cycle with intercooling, reheating and regeneration and are evaluated under the conditions taken from a commercial Siemens SGT-100 turbine.